We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.

+0

# help!

0
321
1

1.

Find constants A and B such that
$$$\frac{x + 7}{x^2 - x - 2} = \frac{A}{x - 2} + \frac{B}{x + 1}$$$
for all x such that x=/=-1 and x=/=2. Give your answer as the ordered pair (A,B).

2.

The function f(x) is defined for 1≤x≤5 as follows:
$$$f(x) = \left\{ \begin{array}{cl} 2x + 1 & \text{if }1 \le x \le 2, \\ 7 - x & \text{if }2 < x \le 3, \\ 10 - 2x & \text{if }3 < x \le 4, \\ 10 - x & \text{if }4 < x \le 5. \end{array}\right.$$$
Find all real numbers x such that f(x)=x.

If you find more than one answer, list them all, separated by commas.

3.

Suppose that
$$$|a - b| + |b - c| + |c - d| + \dots + |m-n| + |n-o| + \cdots+ |x - y| + |y - z| + |z - a| = 20.$$$
What is the maximum possible value of $$|a - n|?$$

4.

The function $$h(x)$$ is defined as:
$$$h(x) = \left\{ \begin{array}{cl} \lfloor 4x \rfloor & \text{if } x \le \pi, \\ 3-x & \text{if }\pi < x \le 5.2, \\ x^2& \text{if }5.2< x. \end{array}\right.$$$
Find $$h(h(\sqrt{2}))$$

Mar 16, 2018
edited by Guest  Mar 16, 2018

### 1+0 Answers

#1
+2

Here's #1 for you:

Collect the terms on right hand side over a common denominator:

$$\frac{A}{x-2}+\frac{B}{x+1}\rightarrow\frac{A(x+1)+B(x-2)}{(x-2)(x+1)}\rightarrow\frac{(A+B)x+A-2B}{x^2-x-2}$$

Compare this with $$\frac{x+7}{x^2-x-2}$$

To make them the same compare the numerators.  It is clear we must have:

A + B = 1   and

A - 2B = 7

Subtract the second from the first to get: 3B = -6  so B = -3

Put this back into the first to get A - 3 = 1  so  A = 4

Hence (A, B) = (4, -3)

For #2

Set x = each term in turn and solve for x.  if the result lies in the range given for each term then that result is valid.  If not it isn't.

For #3

Can't see the whole expression!

For #4

First plug sqrt(2) into h to get, say m = h(sqrt(2))

Then plug m into h to get h(m) which is h(h(sqrt(2)))

.

Mar 17, 2018
edited by Alan  Mar 17, 2018
edited by Alan  Mar 17, 2018